Visual "literacy" : image, mind, and reality - Messaris, Paul (Boulder : Westview Press, 1994)
Post-industrial humankind is inundated daily with visual images. Televisions transmit their blue haze into dark living rooms; advertisements and billboards bombard us at every turn; movies evoke tears, outrage, or hilarity; and the visual arts elicit strong emotional or intellectual responses. At almost every moment, several visual images are warring for our attention in order to make a claim, sell a product, or call us to action. Faced with visual overload, how do we interpret these images? What is happening when a picture moves us? What process takes place in our minds as we respond to such visual devices as close-ups, camera angles, and flashbacks?This book provides a foundation for answering these questions. Encouraging his readers to become “visually literate,” Paul Messaris takes them on a journey through four major conceptual levels of understanding: imparting visual literacy as a prerequisite for comprehending visual media; creating awareness of the general cognitive consequences of visual literacy; making us alert to visual manipulation; and promoting aesthetic appreciation of the images we see. Taken together, these approaches provide a comprehensive view of how visual images are produced and interpreted, and of what their potential social consequences may be.
1. Four aspects of visual literacy : Still images ; Film and television ; Cognitive consequences of visual literacy ; Awareness of artistry and visual manipulation ; 2. The interpretation of still images : Abstract representation ; Concrete representation ; empirical evidence ; 3. The interpretation of film and television : Point-of-view editing ; Editing as an indicator of thoughts and emotions ; The modulation of emphasis and viewer involvement ; Beyond pint-of-view editing ; Propositional editing ; 4. General dognitive consequences of visual literacy : Propositionality revisited ; Representational categories and world views ; Spatial intelligence ; From concrete to abstract to analogy ; 5. Awerteness of artistry and manipulation : The detection of artifice ; Unconcealed artifice ; Visual manipulation ; 6. Conclusion: Other questions, other "literacies" : Images and the appearance of reality ; Images and cultures ; Fammiliarity with visual subject matter ; "Production literacy".
Bibliografija: str. 185-199.
Kazalo.
Keywords: Visual literacy -- United States -- Psychological aspects; Visual communication -- United States -- Psychological aspects; vizualna pismenost; vizualna komunikacija - psihološki aspekti; teorija i filozofija umjetnosti